Natural history of perceived food hypersensitivity and IgE sensitisation to food allergens in a cohort of adults. - Patelis, Antonios; Gunnbjörnsdottir, Maria; Borres, Magnus P; Burney, Peter; Gislason, Thorarinn; Torén, Kjell; Forsberg, Bertil; Alving, Kjell; Malinovschi, Andrei; Janson, Christer (PLoS ONE, 2014)
To access publisher's full text version of this article, please click on the hyperlink in Additional Links field or click on the hyperlink at the top of the page marked Files. No longitudinal studies exist on the natural history of food hypersensitivity and IgE sensitisation to food allergens in adults. To examine the natural history of food hypersensitivity, the natural history of IgE sensitisation to food allergens and to investigate the risk factors for new onset food hypersensitivity. Food hypersensitivity was questionnaire-assessed in 2307 individuals (aged 20-45 years) from Iceland and Sweden during the European Community Respiratory Health Survey both at baseline and follow-up 9 years later. IgE food and aeroallergen sensitisation were assessed in a subgroup of these individuals (n = 807). Values of 0.35 kU/L and above were regarded as positive sensitisation. Food hypersensitivity was reported by 21% of the subjects and this proportion remained unchanged at follow-up (p = 0.58). Fruits, nuts and vegetables were the three most common causes of food hypersensitivity, with a similar prevalence at baseline and follow-up. The prevalence IgE sensitisation to food allergens decreased in general by 56% (p<0.001) and IgE sensitisation to peanut decreased in particular by 67% (p = 0.003). The prevalence of timothy grass IgE sensitisation decreased by 15% (p = 0.003) while cat, mite and birch IgE sensitisation did not decrease significantly. Female sex, rhinitis, eczema and presence of IgE sensitisation to aeroallergens were independently associated with new onset food hypersensitivity. The prevalence of food hypersensitivity remained unchanged while the prevalence of IgE sensitisation to food allergens decreased in adults over a 9-year follow-up period. The decrease in prevalence of IgE sensitisation to food allergens was considerably larger than the change in prevalence of IgE sensitisation to aeroallergens.